Three years of measurements of first year ridges in the Barents Sea and fram strait - Sand, Björnar; Bonath, Victoria; Sudom, Denise; Petrich, Christian (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2015)
During three expeditions in March 2011, March 2012 and April/May 2013 with the Norwegian coastguard vessel "KV Svalbard", two pressure ridges around Svalbard, one ridge in Fram Strait and three ridges in Olga strait have been studied with respect to ridge geometry and physical and mechanical properties. With a discrete measurement, which is of most interest here, information can be obtained on the overall size and shape of an individual ridge at one particular location, both above and below the waterline. This approach provides detailed quantitative information on both the sail and keel size and shape, of a specific ridge, as well as its porosity. It does not supply any information on ridge spacing. The results of individual profile measurements are discussed. Measurements of vertical profiles along the spine and transects perpendicular to the spine are presented for these ridges. The sail height, sail width, keel depth and keel width, consolidated layer thickness, rubble block sizes and porosities are examined for each ridge. The results presented in this paper contribute to more data in terms of geometry and morphology of the first-year ridge off Svalbard, in Fram Strait and Barents Sea. Compression and tensile strength properties are important input data for constitutive modelling. Still strength properties of ridged ice are not yet sufficiently investigated. Uniaxial compressive tests were performed with horizontal and vertical loading directions and the results from the testing of level ice and consolidated layer are summarized with consideration of total porosity. Godkänd; 2015; 20151001 (andbra)